A novel polyionic liquid with lubricity and viscosity-increasing dual functionalities as the additive in aqueous lubrication system - Bo Yu; Kun Zou; Rui Wang; Qiang Chen; Rui Dong; Xiao Liu; Jiaying Zhang; Wenquan Lv; Qiangliang Yu; Meirong Cai; Feng Zhou (Friction)
Abstract The polyionic liquid poly-PEGMA-r-METAC (PPM) with quaternary ammonium has been synthesized and evaluated as additive in aqueous lubricating fluids. The rheological behavior of aqueous lubricating fluids with PPM has been characterized to confirm PPM’s function as a viscosity modifier. The tribological behavior of aqueous lubricating fluids with PPM has been investigated on SRV-V and MTM testing machines. It was found that PPM has excellent viscosity-increasing, lubricating, and anti-wear properties as an additive for aqueous, which can be attributed to the ability of PPM to form the protective film and boundary tribofilm generated from complex tribochemical reaction on rubbing surface. The obtained PPM with dual functions of anti-corrosion additives and viscosity index improver can play an important role in diverse lubrication regimes.